Arthroscopic anterior cruciate ligament repair with and without suture augmentation: technical note. Issue 4 (15th February 2021) - Batista, Jorge Pablo; Chahla, Jorge; Dalmau-Pastor, Miki; Maestu, Rodrigo; Kunze, Kyle N; Guelfi, Matteo
Abstract : Anterior cruciate ligament (ACL) tears are routinely treated with an ACL reconstruction. This is based on historical literature reporting high failure rates after ACL repairs in addition to the limited healing potential of the ACL. Recently, improved understanding of pathophysiology of ligamentous healing has led to increasing interest in treating proximal avulsions with excellent tissue quality in the acute setting, as this technique allows for ACL healing. Potential advantages of ACL repair include preservation of native proprioceptive and kinematics of the knee, avoidance of graft harvesting morbidity and the possibility to perform a primary ACL reconstruction in case of failure. As a consequence, several techniques for ACL repair have been proposed that can be performed in isolation or with suture augmentation. The primary aim of this technical note is to describe step-by-step the ACL repair technique with and without suture augmentation. The secondary aim of the current study is to review the indications, patient selection and advantages of the technique.